Worker heat stress prevention and work metabolism estimation: comparing two assessment methods of the heart rate thermal component. Issue 8 (3rd August 2019) - Dubé, Philippe-Antoine; Imbeau, Daniel; Dubeau, Denise; Auger, Isabelle
Abstract: The heart rate thermal component ( Δ H R T ) can increase with body heat accumulation and lead to work metabolism (WM) overestimation. We used two methods (VOGT and KAMP) to assess Δ H R T of 35 forest workers throughout their work shifts, then compared Δ H R T at work and at rest using limits of agreement (LoA). Next, for a subsample of 20 forest workers, we produced corrected WM estimates from Δ H R T and compared them to measured WM. Although both methods produced significantly different Δ H R T time-related profiles, they yielded comparable average thermal cardiac reactivity (VOGT: 24.8 bpm °C −1 ; KAMP: 24.5 bpm °C −1 ), average Δ H R T (LoA: 0.7 ± 11.2 bpm) and average WM estimates (LoA: 0.2 ± 3.4 ml O2 kg −1 min −1 for VOGT, and 0.0 ± 5.4 ml O2 kg −1 min −1 for KAMP). Both methods are suitable to assess heat stress through Δ H R T and improve WM estimation. Practitioner summary: We compared two methods for assessing the heart rate thermal component ( Δ H R T ), which is needed to produce a corrected HR profile for estimating work metabolism (WM). Both methods yielded similar Δ H R T estimates that allowed accurate estimations of heat stress and WM at the group level, but they were imprecise at the individual level. Abbreviations: AIC: akaike information criterion; bpm: beats per minute; CI: confidence intervals; CV: coefficient of variation in %; CV drift: cardiovascular drift; ΔHRT : the heart rate thermal component in bpm; ΔHRT : the heart rate thermal component in bpm; ΔΔHRT : variation in the heart rate thermal component in bpm; ΔTC : variation in core body temperature in °C; HR: heart rate in bpm; HRmax: maximal heart rate in bpm; Icl: cloting insulation in clo; KAMP: Kampmann et al. (2001) method to determe ΔHRT ; LoA: Limits of Agreement; PMV-PPD: the Predicted Mean Vote and Predicted Percentage Dissatisfied; PHS: Predicted Heat Strain model; RCM: random coefficients model; SD: standard deviation; TC: core body temperature in °C; TCR: thermal cardiac reactivity in bpm °C −1 ; τΔHRT : rate of change in the heart rate thermal component in bpm min −1 ; τTC : rate of change in core body temperature in °C min −1 ; tα, n-1 : Student's t statistic with level of confidence alpha and n −1 degrees of freedom; TWL: Thermal Work Limit model; V ̇ O 2 : oxygen consumption in ml O2 kg −1 min −1 ; V ̇ O 2 max: maximal oxygen consumption in ml O2 kg −1 min −1 ; VOGT: Vogt et al. (1973) method to determine ΔHRT ; WBGT: Wet-Bulb Globe Temperature in °C; WM: work metabolism